Malaria and dyserythropoiesis: a mini review - Liu, Fang-Fang; Li, Ke (Frontiers in Cellular and Infection Microbiology, 2025)
Malaria associated anemia is increasingly recognized as a consequence not only of red cell destruction but of profound, parasite driven disruption of erythropoiesis within the bone marrow niche. Here, we synthesize recent in vitro, ex vivo, clinical and postmortem studies to construct a unified mechanistic framework in which four interlocking pathways converge to produce dyserythropoiesis. First, a cytokine storm dominated by IL-6, TNF-α, IFN-γ and MIF suppresses erythropoietin synthesis, upregulates hepcidin and diverts erythroid progenitors toward myeloid fate via destabilization of GATA-1. Second, hemozoin crystals catalyze Fenton chemistry and lipid peroxidation, generating 4-hydroxynonenal adducts that cripple GATA-1 and trigger mitochondrial apoptosis of erythroblasts. Third, Plasmodium parasites preferentially infect orthochromatic erythroblasts, prolonging a 10-day gametocyte maturation cycle beyond the host’s 3–4-day enucleation window and releasing extracellular vesicles that arrest terminal differentiation. Fourth, hemozoin-laden macrophages remodel erythroblastic islands, precipitating local iron restriction and sustained oxidative stress. Together these processes create a “developmental sanctuary” that favors parasite persistence while crippling host erythropoiesis. We also highlight emerging single-cell and spatial-omics technologies, together with 3-D bone-marrow organoids, as platforms for dissecting spatiotemporal parasite–host interactions and for testing niche-targeted therapies aimed at reversing ineffective erythropoiesis.